Patient selection for transcatheter aortic valve implantation (TAVI) in South Africa - Thomas, Martyn; Mabin, Thomas A. (SA Heart Journal, 2017)
Patient selection is likely to be the most important determinant of a successful long term outcome of the TAVI procedure. It requires careful assessment of the indications for aortic valve replacement, clinical status of the patient, associated co-morbidities and, importantly, the cognitive function and motivation of the patient. This assessment must be made by a multi-disciplinary team consisting of at least a cardiologist, cardiac surgeon, anaesthetist and general physician. Careful imaging of the relevant anatomy with ultrasound and CT scanning is critical. Experience improves patient selection and ultimate outcome. Funding remains a challenge and many patients worthy of the procedure are denied because of costs.